Implementasi Adaptasi Teknologi Dalam Program Kampus Mengajar Bagi Sekolah Terdampak Pandemi Covid-19 di Sekolah Dasar Negeri Latang Kabupaten Alor - Abdul Syukur; Dwi Alya R.R Kurnia; Mariana Ikun RD Pareira (Jurnal Kelimutu Pengabdian Masyarakat, 2022)
The objectives of the Teaching Campus Program include increasing empathy or social sensitivity to existing problems, honing thinking and collaboration skills, developing insight, character, and soft skills, increasing the role and contribution and service of students as academia to national education. The Teaching Campus Program (KM) is an activity carried out for approximately 5 months, where in its implementation students go directly to schools affected by the COVID-19 pandemic. Activities carried out by students include assisting teachers in teaching, assisting teachers in adapting technology, and assisting school administration. The focus in this paper is only on adapting technology which is considered the most important in the implementation of online learning for both teachers and students. The results of implementing the technology adaptation of the Teaching Campus Program include students getting good preparation in facing ANBK (Computer-Based National Assessment), teachers can operate computers, especially office applications (word, powerpoint and ecxel) and can operate infocus as a tool in the learning process. While what students get is experience in program making starting from identification, program design preparation, implementation to program evaluation. In the end, the conclusion from the implementation of this program is that students and teachers are assisted in the implementation of the teaching and learning process during the covid-19 pandemic. The same is felt by students, where students can implement the knowledge that has been obtained on campus for the benefit of the community. Keywords: Teaching Campus, Technology Adaptation. Abstrak Tujuan Program Kampus Mengajar diantaranya adalah menambah empati atau kepekaan sosial terhadap permasalahan yang ada, mengasah keterampilan berpikir dan bekerjasama, mengembangkan wawasan, karakter, dan soft skill, meningkatkan peran dan kontribusi serta pengabdian mahasiswa sebagai civitas akademisi terhadap pendidikan nasional. Program Kampus Mengajar (KM) adalah suatu kegiatan yang dilakukan selama kurang lebih 5 bulan, dimana dalam pelaksanaannya mahasiswa turun langsung ke sekolah terdampak pandemi covid-19. Kegiatan yang dilakukan oleh mahasiswa diantaranya membantu guru dalam mengajar, membantu guru dalam adaptasi teknologi, serta membantu administrasi sekolah. Fokus pada tulisan ini hanya pada adaptasi teknologi yang dianggap paling penting dalam pelaksanaan belajar secara daring baik bagi guru maupun peserta didik. Hasil penerapan adaptasi teknologi Program Kampus Mengajar diantaranya adalah siswa mendapatkan persiapan yang baik dalam menghadapi ANBK (Assesmen Nasional Berbasis Komputer), guru dapat mengoperasikan komputer khususnya aplikasi office (word, powerpoint dan ecxel) serta dapat pengoperasian infocus sebagai alat dalam proses pembelajaran. Sedangkan yang didapatkan oleh mahasiswa adalah pengalaman dalam pembuatan program mulai dari identifikasi, penyusunan rancangan program, pelaksanaan sampai dengan evaluasi program. Pada akhirnya, kesimpulan dari dilaksanakannya program ini adalah para peserta didik dan guru terbantu dalam pelaksanaan proses belajar mengajar selama pandemi covid-19. Hal yang sama juga dirasakan oleh mahasiswa, dimana mahasiswa dapat mengimplementasikan ilmu yang selama ini didapatkan di kampus untuk kemaslahatan masyarakat. Kata kunci: Kampus Mengajar, Adaptasi Teknologi.